Hubungan Paparan Merkuri (Hg) Dengan Gangguan Fungsi Tiroid Pada Penambang Emas Tradisional Di Desa Jendi Kecamatan Selogiri Kabupaten Wonogiri - Hananingtyas, Izza; Suhartono, Suhartono; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2013)
Background: Mercury was released in environment as a result of human activities such as the traditional gold mining industry. The activities of traditional gold mining used amalgam processes that cause negative effects of mercury which exposured to traditional gold miners. Chronic effects of mercury exposure  due to obstruction of iodine uptake by mercury in the body, so that it disrupt thyroid function. It was caused by inhibition of secretion levels of T3 and T4, and  increased activity of TSH, as feedback synthesis and secretion of thyroid hormone. The purpose of this study was determine the relationship between mercury exposure with disfunction thyroid in traditional gold mining workers in the Village Jendi, Selogiri District, Wonogiri. Method:It was an observational research using cross-sectional design. The subject were 42 traditional gold miners in Jendi Selogiri Village, Wonogiri, which purposively selected. The instrument used  are questionnaires and laboratory analysis of blood and urine specimens. Data obtained from TSH, FT4 serum, Hg in blood, urinary iodine excretion, and measurement of nutritional status. Data would be analyzed using chi squar and regression logistic. Result: The research results showed that there was no correlation between level of  Hg in blood (p=0,800) , work period (p=0,101), work duration (p=0,594) and there was no different of disfunction thyroid by oocupation (p=0,853), with range of  Hg in blood 4,4 to 9,373 ppm. Conclusion: This study concluded that, there was no association between mercury exposure with disfunction thyroid in the traditional gold miners in Jendi, Selogiri District, Wonogiri.   Keyword : mercury, thyroid disfunction, TSH, FT4